The specifics of narrative in the discourse of Svetlana Alexievich: pro et contra - Gubskaya, Olga N. (Journal of the Belarusian State University. Philology, 2021)
The article deals with the issues of genre definition of Svetlana Alexievich’s works. An overview of the research position on the above issue is proposed. The author demonstrates the views of both Belarusian and foreign scientists, who unanimously declare the absence of pure documentaries in the creation of S. Alexievich. At the same time, it is emphasized that modern literary critics do not have a clear position for determining the genre of the writer’s works. Hybrid genre and meta-genre are terms which are currently operational with the regard to the abovementioned problem. It is proved that the presence of elements of artistry in the writer’s discourse is an obvious feature of her way of narration. Taking into account the idea of meta-artistic fact in the context of a literary work, the specificity of naration in the discourse of S. Alexievich is investigated. The role of fact in the author’s text of the writer is analyzed. Using the semiotic methodology, a narratological analysis of the structure of its texts is carried out. As a result of this analysis, it is concluded that the final product of the writer is the sum of contexts that connect a real fact of the past (a historical event), the same fact in a reinterpreted form (a narrative event) and the new content of these phenomena transformed through the prism of the author’s consciousness. It is proved that the works of Svetlana Alexievich are texts in the text, which gives them a special narrative specificity. A double treatment of the fact becomes obvious: first directly in the mind of the narrator – a participant in real historical events, then in the mind of a specific author who interprets the narrative event into narration and his own discourse. As a result, a system of codes is formed, which the writer uses to give her texts a new cultural meaning. The purpose of this article is to demonstrate the discovery of a new cultural meaning in the works that made up S. Alexievich’s pentateuch «Voices of Utopia».
Keywords: fact; narrative event; historical event; system of semiotic signs; cultural memory; meta genre